BASIC PSYCHOLOGICAL NEEDS, MOTIVATION, AND FOREIGN LANGUAGE VOCABULARY LEARNING STRATEGIES AND SKILLS OF INDONESIAN UNIVERSITY STUDENTS - Susanto, Alpino; Oktavia, Yunisa; Kumalasari, Tety; Silitonga, Frangky (International Journal of Education, 2024)
Foreign language vocabulary learning can be pursued if the students have motivation and interest in which psychological factors play an important role in enacting learning strategies toward increased skills. This study aims to examine the integrated process model of the BasicPsychological Needs (BPN) variable as a behavioural phenomena in relation to autonomous and controlled motivation individually or collectively toward Vocabulary Learning Strategies (VLSs) and Vocabulary Skills (VSs). A total of 186 students of one university participated in this research. The Basic Psychological Needs of Second Language Scale (BPNSLS) was employed to assess the BPN, meanwhile the Self-Determination Theory of Second Language Scale (SDTSLS) was to assess the autonomous and controlled motivation. There are three questionnaires (BPNSLS, SDTSLS, VLSs) were adopted and adapted of the previous study. The fourth research instrument was Vocabulary Level Test (VLT) version b to assess vocabulary skills. A partial least square was used to contest the research model. The structural model of the relationship between the variables of basic psychological needs, self-determination theory, vocabulary learning strategies, and vocabulary mastery, revealed that vocabulary learning strategies play a crucial role in looking at the influence of motivational orientation on vocabulary skills described in the proposed model. This study suggests that further research can explore more on how motivation relates to learning strategies in general and comparing between autonomous versus controlled motivation.